Hemodynamic study on upper extremity: Simulation on straight reverse saphenous vein graft - Shahriman, Abu Bakar, Dr,; Muhd Nur Rahman, Yahya; Siti Khadijah, ZA'BA, Dr,; Wan Khairunizam, Wan Ahmad, Dr,; Abdul Halim, Ismail; Khairul, A. H.; Sharifah Roohi, Syed Waseem Ahmad (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/